Preventing Cyberbullying in Language Classrooms Among Level 100 Tertiary Students: Creating the Awareness of Its Prevalence and Effects on Students - James, Zinteng; Fuseini, Miftawu; Deo-Donne, Puoza; Issah, Sadik (Integrated Journal for Research in Arts and Humanities, 2023)
Bullying of any kind violates the fundamental human rights of students in language classrooms. Cyberbullying is the use of technology to intimidate and harass students. This kind of bullying occurs on the internet and causes students to suffer from depression, low self-esteem and intellectually marginalized in the language classroom. This paper makes provision for the general populace to appreciate the prevalence rate, the effect and provide innovative ways to remedy cyberbullying while encouraging the responsible use of technological tools. A cross-sectional study including a sample of 100 participants (from level 100) aged 19 to 25 years was used in this study. The study focused on tertiary students, aged 19-25 years old, since previous research have indicated that this age group is more likely to be involved in cyberbullying and victimization in higher learning environments. Consent of the students was obtained and responses to the various items were treated with confidentiality. The participating schools were randomly selected from a list of all of the public tertiary schools in the northern zone and displayed different socioeconomic backgrounds. Results indicated that cyberbullying was associated with academic problems, low self -esteem and depression among tertiary students. Evidence -based bullying prevention programs such as education and parental involvement are good ways to reduce the incidences of cyberbullying in the future. More research is needed to effectively design a successful, targeted prevention program suitable for students in tertiary institutions and players in the language classroom.